2014
DOI: 10.1016/j.tranon.2014.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Salinomycin Treatment Results in Resistance Formation through Clonal Selection of Epithelial-Like Tumor Cells

Abstract: Acquiring therapy resistance is one of the major obstacles in the treatment of patients with cancer. The discovery of the cancer stem cell (CSC)–specific drug salinomycin raised hope for improved treatment options by targeting therapy-refractory CSCs and mesenchymal cancer cells. However, the occurrence of an acquired salinomycin resistance in tumor cells remains elusive. To study the formation of salinomycin resistance, mesenchymal breast cancer cells were sequentially treated with salinomycin in an in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 50 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…Such models can be used to study processes that cannot be studied in cell lines. In this context, acquired resistance models have been established based on cell line-and patient-derived xenografts, organoids, and transgenic tumour models [115][116][117][118][119][120][121][122][123][124][125] . However, cell lines enable the establishment of a substantially larger number of models within a given timeframe and at a given cost, which is critical for studying the drug-induced heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Such models can be used to study processes that cannot be studied in cell lines. In this context, acquired resistance models have been established based on cell line-and patient-derived xenografts, organoids, and transgenic tumour models [115][116][117][118][119][120][121][122][123][124][125] . However, cell lines enable the establishment of a substantially larger number of models within a given timeframe and at a given cost, which is critical for studying the drug-induced heterogeneity.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike in several molecular evolution assays we performed with doxorubicin, the growth retardation here was only modest. A recent study by Kopp et al also showed that consecutive treatment of mesenchymal breast cancer cells with salinomycin resulted in resistance formation by mesenchymal to epithelial transition (MET) (27).…”
Section: Discussionmentioning
confidence: 99%
“…Cells (80% of confluency) were treated with salinomycin (Sigma-Aldrich, Germany) for 72 h as previously described (26). The concentration of salinomycin was 500 nM for the MCF-7 and BT-474 cells and 50 nM for the MDA-MB 231 and MDA-MB 436 cells as mesenchymal cells display increased sensitivity to salinomycin (16,27). Thereafter, the treatment medium was replaced with fresh medium and cells were grown until recovery (80% of confluency).…”
Section: Methodsmentioning
confidence: 99%
“…A synergistic effect between salinomycin and conventional chemotherapeutic drugs that target cycling cells has been demonstrated 36,37 as well as the development of resistance to salinomycin. 38 …”
Section: Discussionmentioning
confidence: 99%